IJCM_280A: A prospective study on safety and clinical efficacy of rabies biologicals in paediatric patients with category III animal exposure - Fotedar Nidhi; Ravish HS (Wolters Kluwer Medknow Publications, 2024)
Background: Rabies remains a significant public health concern worldwide, particularly among paediatric populations who are vulnerable to animal exposures. This prospective study aimed to assess the safety and clinical efficacy of rabies biologicals in pediatric patients following Category III animal exposures. Objectives: 1. To describe the post exposure prophylaxis provided to the animal bite victims at the anti rabies clinic. 2. To asses the safety and clinical efficacy of currently available rabies biologicals for post exposure prophylaxis. Methodology: A prospective study was undertaken enrolling 289 pediatric patients fulfilling eligibility criteria who presented with Category III animal exposures at the anti-rabies clinic of KIMS Hospital and Research Centre, Bangalore. All the subjects received rabies biologicals as per NCDC guidelines. The details pertaining to socio demographic profile, biting animal, characteristics of wound, details of post exposure prophylaxis provided were recorded. All the study subjects were followed up for immediate and delayed adverse events. Subsequently, all were followed up for 6 months to demonstrate the clinical efficacy of PEP. Results: The mean age of study subjects was 9.4 years and most of them (43%) were going to school. Dog was the predominant biting animals (96.6%) with most bites were abrasions (45%), mainly on the lower limbs (42%). Single RmAb was the most commonly administered passive immunization (67%) and PVRV was the predominant vaccine (65%). Adverse events following post-prophylaxis were primarily local, predominantly pain (13.2%) and there were no systemic events. All the subjects were alive and healthy at the end of 6 months following PEP. Conclusion: This study contributes valuable insights into the safety and clinical efficacy of rabies biologicals in a pediatric cohort following Category III animal exposures, supporting the continued use of these biologicals in pediatric patients.